The Impact of Water Resource Deterioration on the Reassessment of International Agreements on Transboundary Rivers, Shatt Al-Arab as a Case Study - Thaer Ahmed Al-Fadhli , Researcher. Zahra; Abdul-Ameer Rashm Al-Asadi , Prof. Dr. Safaa (Basra studies journal, 2025)
The present study aims at revealing the extent of environmental deterioration (particularly hydrological) to which Shatt al-Arab downstream area was subjected after the conclusion of the Algiers Agreement between Iraq and Iran in 1975. The 1975 Algiers Accord focused on the demarcation of river boundaries and freedom of international navigation downstream without considering the importance of sustaining the flow of fresh water, protecting the aquatic environment from pollution and ensuring it for future generations. In light of the severe environmental deterioration in the downstream area and its negative repercussions on various aspects of life in Basrah, and based on the change in international law, which stipulates those agreements related to international rivers should include a principle that emphasizes the need to maintain waterways and sustain the flow of fresh water and preserve it for future generations. Therefore, it is possible to demand a reassessment of the terms of the Algiers Accord and amendments to suit the human changes and the great nature that the region has been exposed to after about half a century of its conclusion.